(untitled) (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This study aims to examine the reality of divorce in Sungguminasa Gowa, the rational reasons for wives suing for divorce from their husbands and the public’s perception of the reality of divorce in Sungguminasa Gowa as well as the study of Tasri philosophy on the logic of the benefits of divorce by wives. The method used in this study is a case study approach by collecting data on divorce lawsuits at the Sungguminisa Religious Court, Gowa Regency, then directly interviewing the divorce perpetrators and judges of the Sungguminasa Religious Court, Gowa Regency. The data analysis method used is an analysis of Islamic legal philosophy which aims to reveal the reasons for the benefit of a wife suing for divorce from her husband. The findings of the study stated that benefits are the main reason for a wife to sue for divorce from her husband and the benefits of the wife are classified into three levels of benefits, namely benefits that are daruriy, benefits that are hajjiy and benefits that are tahsiniy. Domestic violence (KDRT) experienced by the wife is a manifestation of the benefits for the wife in suing for divorce from her husband because the domestic violence can threaten the life of a wife. Biological needs are the embodiment of the benefits of hajjiyat for the wife, so the wife sues for divorce from her husband because biological needs are something that the wife needs. Economic sufficiency is the embodiment of the benefits of tahsiniy for the wife because economic needs are a complement and perfection of a wife’s social life. The results of the study stated that divorce cases at the Sungguminasa Religious Court from 2021 to 2023 have increased.